Analysis of routinely collected data: Determining associations of maternal risk factors and infant outcomes with gestational diabetes, in Pakistani, Indian, Bangladeshi and white British pregnant women in Luton, England. (March 2021) - Garcia, Rebecca; Ali, Nasreen; Guppy, Andy; Griffiths, Malcolm; Randhawa, Gurch
Abstract : Objective: This study aims to compare the prevalence of gestational diabetes in Indian, Pakistani, Bangladeshi and British women in Luton, England and further examine associations in maternal risk factors (age BMI, smoking status and birth outcome), with gestational diabetes, with maternal ethnicity. Design: A retrospective analysis using routinely collected secondary data from Ciconia Maternity information System (CMiS), between 2008 and 2013. The ethnicity of women recorded as Indian, Pakistani, Bangladeshi and white British, residing in [removed] were included in the study. The outcomes for n =15, 211 cases were analysed using adjusted standardised residuals, Pearson Chi-square, frequencies and percentages of women with gestational diabetes. Results: The prevalence of gestational diabetes was significantly higher in the sample of Bangladeshi (2.1%) and Pakistani (1.4%) compared to Indian (1%) and white British (0.4%) women. Of the women diagnosed with gestational diabetes, 48.7% of the women diagnosed with gestational diabetes in this cohort were Pakistani, compared with 28.3% of Bangladeshi, 6.6% of Indian and 16.4% of white British (χ2= 84.57 df=6, p<0.001). A number of significant Pearson Chi-square associations were found between Pakistani women diagnosed with gestational diabetes and BMI over 30kg/m 2 ( χ 2 = 43.1 df =4, p <0.001) and an early gestational age at delivery (24-37 weeks) (χ2 = 4.084 df =1, p =0.043). Conclusions: There are important differences in the prevalence rates of gestational diabetes which varied by maternal ethnicity. Of the women who had GDM, 48.7% were Pakistani, compared with 28.3% Bangladeshi, 16.4% white British and 6.6% Indian. It is essential policy makers and service providers target GDM screening and associated interventions and future research seeks to understand the reasons behind these differences.